Reflections on strategies for university supervision in special education - Bussey, Heidi; Lay, Celina Dulude (Frontiers in Education, 2023)
University supervisors for special education teachers are preparing teacher candidates to have many roles and responsibilities and to collaborate with many stakeholders, even as they begin their field experiences. In this self-study of teaching and teacher educator practice (S-STTEP), we examined the narrative reflections of a university professor in her role as a university professor and supervisor for special education student teachers. We wondered what particular diagnostics or tools for supporting teacher candidates would be uncovered. We also wondered if other strategies within the role of university supervisor in the field of special education would emerge.